What people post during pandemic? A content analysis of Malaysian's Instagram posts during movement control order (MCO) 3.0 - Lee, Jamie (2022)
For the COVID-19 pandemic, Malaysia has implemented MCO 3.0 to control the transmission of Covid-19 variant virus infections in the public and prevent a rapid spike in cases, due to the rising trend of daily Covid-19 variant virus cases. In time Malaysia is also waiting for vaccines. MCO 3.0 had a similar controlling effort as the vaccine when it was implemented. During MCO 3.0, there have been traditional media portrayals of suicide cases and the White Flag Movement. It seems that everyone is miserable. Thus, this study was conducted to investigate if the doom and gloom was reflected through social media and the general sentiment's impact on marketing and media implication. This research is a content analysis study that aims to determine the type of content that Malaysians posted on Instagram during the Movement Control Order (MCO) 3.0 period and analyse their sentiment reflected in the Instagram posts. A total of 150 popular posts were collected on Instagram and filtered using the hashtags "#mco3" and "#mco2021". In this study, the content analysis method was used in conjunction with a qualitative methodology. There are 9 image categories and 5 caption categories in this study. The 5 caption categories include the narrative of fear, the narrative of fun, the narrative of sadness, the narrative of responsibility, and the narrative of encouragement. According to the findings of this study, most Malaysians post portrait images on Instagram during MCO 3.0, and most of them express narrative of responsibility in their Instagram captions. This study will be able to provide business owners some insight into how to provide goods and services that are relevant to Malaysians' lifestyles and demands. Instagram has also become the finest choice for marketers to promote their brand image to consumers since it has become one of the most popular communication channels in recent years. Thus, business owners will have a better understanding of their customers' demands and motivations when it comes to using Instagram, which will aid them in figuring out how to fulfil them and improve their brand relationship.